2016
DOI: 10.1097/bpo.0000000000000649
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Obesity Increases the Risk of Failure in the Treatment of Distal Forearm Fractures

Abstract: Background: Childhood obesity is a national problem that has gained significant attention in both the medical literature and the national media. Obesity in the adult population has been associated with increased failure of conservative treatments. Our hypothesis is that childhood obesity is associated with a loss of reduction after closed treatment of distal radius fractures. Methods: A total of 157 patients with consecutive distal radius fractures who underwent closed reduction in the emergency department or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 11 publications
0
11
2
1
Order By: Relevance
“…This enabled us to perform extensive analysis on the association between ICS use in asthmatic patients and fracture risk factors. This was particularly useful here as recent studies have shown BMI to be associated both with the severity of asthma symptoms, as well as an increased risk of fractures in general …”
Section: Discussionmentioning
confidence: 99%
“…This enabled us to perform extensive analysis on the association between ICS use in asthmatic patients and fracture risk factors. This was particularly useful here as recent studies have shown BMI to be associated both with the severity of asthma symptoms, as well as an increased risk of fractures in general …”
Section: Discussionmentioning
confidence: 99%
“…There is current debate and conflicting studies as to whether increased adiposity leads to larger bones, increased or decreased density, or increased fractures rates (Table 1). Not only are obese children more likely to have fractures but once they do, these children have a higher rate of improper bone reductions and require more subsequent manipulations to correct the misaligned bones [49]. Additionally, children with higher BMIs have a greater prevalence of open reduction surgery to repair their factures [49], which leads to increased surgery complications [50] and more cosmetic scarring compared to closed reductions.…”
Section: Main Textmentioning
confidence: 99%
“…Not only are obese children more likely to have fractures but once they do, these children have a higher rate of improper bone reductions and require more subsequent manipulations to correct the misaligned bones [49]. Additionally, children with higher BMIs have a greater prevalence of open reduction surgery to repair their factures [49], which leads to increased surgery complications [50] and more cosmetic scarring compared to closed reductions. Fueling further complexity, it has also been shown that where the deposition of adiposity is localized also has an impact on bone strength.…”
Section: Main Textmentioning
confidence: 99%
“…The rates of redisplacement in cast have been reported to range from 21 to 39% after acceptable initial reduction [10,11]. Factors that have been implicated in loss of reduction in children are numerous, and different studies undertaken to define their roles have not been able to give convincing results [12][13][14][15].…”
mentioning
confidence: 99%